Nrg1 regulates cortical wiring and motor recovery upon traumatic injury - González-Manteiga, Ana; Navarro-González, Carmen; Rodríguez-Prieto, Ángela; Zavaglia, Maria Vittoria; Fazzari, Pietro (Frontiers in Cellular Neuroscience, 2026)
IntroductionTraumatic brain injury (TBI) is a leading cause of disability, yet molecular mechanisms supporting cortical repair remain poorly defined. While Neuregulin 1 (Nrg1) is essential for cortical development, its role in traumatic cortical injury in adults is unclear.MethodsTo circumvent developmental confounds, we used an inducible conditional Nrg1 knockout in the adult mouse and subjected it to controlled cortical damage (CCD) in the motor cortex. We combined high-resolution adeno-associated viral tracing of callosal projections with comprehensive behavioral, histological, and molecular analyses.ResultsNrg1 deletion led to significant impairments in structural connectivity and motor recovery, which were markedly exacerbated in mature mice, indicating a critical role for Nrg1 in adult cortical repair. Mechanistically, our data indicate that Nrg1 promotes this plasticity through intracellular domain (ICD) signaling, acting cell-autonomously to enhance axonal outgrowth in neuronal cultures. Furthermore, loss of Nrg1 was associated with altered perineuronal net (PNN) structure and increased neuroinflammation at the lesion site.DiscussionThese findings identify endogenous Nrg1 as a key regulator of structural preservation and functional recovery after cortical injury, highlighting Nrg1 signaling as a potential target to enhance cortical plasticity following trauma.